A hidden battle in the dirt: Soil amoebae interactions with Paracoccidioides spp. - Patrícia Albuquerque; André Moraes Nicola; Diogo Almeida Gomes Magnabosco; Lorena da Silveira Derengowski; Luana Soares Crisóstomo; Luciano Costa Gomes Xavier; Stefânia de Oliveira Frazão; Fernanda Guilhelmelli; Marco Antônio de Oliveira; Jhones do Nascimento Dias; Fabián Andrés Hurtado; Marcus de Melo Teixeira; et al. (Public Library of Science (PLoS), 2019)
Paracoccidioides spp. are thermodimorphic fungi that cause a neglected tropical disease (paracoccidioidomycosis) that is endemic to Latin America. These fungi inhabit the soil, where they live as saprophytes with no need for a mammalian host to complete their life cycle. Despite this, they developed sophisticated virulence attributes allowing them not only to survive in host tissues but also to cause disease. A hypothesis for selective pressures driving the emergence or maintenance of virulence of soil fungi is their interaction with soil predators such as amoebae and helminths. We evaluated the presence of environmental amoeboid predators in soil from armadillo burrows where Paracoccidioides had been previously detected and tested if the interaction of Paracoccidioides with amoebae selects for fungi with increased virulence. Nematodes, ciliates, and amoebae-all potential predators of fungi-grew in cultures from soil samples. Microscopical observation and ITS sequencing identified the amoebae as Acanthamoeba spp, Allovahlkampfia spelaea, and Vermamoeba vermiformis. These three amoebae efficiently ingested, killed and digested Paracoccidioides spp. yeast cells, as did laboratory adapted axenic Acanthamoeba castellanii. Sequential co-cultivation of Paracoccidioides with A. castellanii selected for phenotypical traits related to the survival of the fungus within a natural predator as well as in murine macrophages and in vivo (Galleria mellonella and mice). These changes in virulence were linked to the accumulation of cell wall alpha-glucans, polysaccharides that mask recognition of fungal molecular patterns by host pattern recognition receptors. Altogether, our results indicate that Paracoccidioides inhabits a complex environment with multiple amoeboid predators that can exert selective pressure to guide the evolution of virulence traits.